2021
DOI: 10.1080/09613218.2021.2004386
|View full text |Cite
|
Sign up to set email alerts
|

Patient well-being, adaptation of and to indoor conditions, and hospital room design: two mixed methods case studies

Abstract: Research indicates that adaptation influences how people experience indoor conditions (ICs), and that the built environment influences both adaptation, via perceived control, and well-being. Their interlinkage is, however, not well understood. Therefore, we investigated how the design of hospital rooms can contribute to patients' well-being by supporting their adaptation of and to ICs via perceived control. Two mixed methods case studies were conducted at hospital wards in Belgium, each concurrently collecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…First, designers can increase comfort by stimulating perceived control, via adaptable and static building characteristics. Within the larger research project this study is part of, we observed, e.g., that patients like the possibility to dim the lighting, or perceive more control in double rooms where they reside face-to-face instead of next to each other (Willems et al 2021).…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…First, designers can increase comfort by stimulating perceived control, via adaptable and static building characteristics. Within the larger research project this study is part of, we observed, e.g., that patients like the possibility to dim the lighting, or perceive more control in double rooms where they reside face-to-face instead of next to each other (Willems et al 2021).…”
Section: Discussionmentioning
confidence: 92%
“…The grouping built on the adaptation strategies identified by Willems et al (2021) and mentioned in the introduction, but differs slightly from it. We focused only on adaptation strategies that differ in how patients interact with indoor conditions via adaptable building characteristics.…”
Section: Grouping Respondents Per Adaptation Strategymentioning
confidence: 99%
See 3 more Smart Citations